Optimal Control Problem Governed by an Evolution Equation and Using Bilinear Regular Feedback - Badriah Shuwaysh Alanazi; Maawiya Ould Sidi (Journal of Mathematics)
We solve an optimal control problem governed by an evolution equation using bilinear regular feedback. Using optimization techniques, we show how to approximate the flow of a reaction-diffusion bilinear system by a desired target. For application, we consider the regional flow problem constrained by a bilinear distributed system. The paper ends by an example illustrating the numerical approach of the proposed method.